Analysis of caesarean delivery rates using the ten group classification system in a tertiary care hospital - Panicker, Seetha; T.V., Chitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: With the increasing safety of operative delivery the caesarean section rates have been increasing steadily over the last 60 years both in the developing countries and the developed world. However efforts to analyse the rates and identify preventable causes are difficult as most units report only the overall caesarean section rates. This retrospective study was undertaken to analyse the indications for caesarean delivery in a one year period from January 1st to December 31st 2014 using the Robson’s ten group classification system to identify CS rates in each of the separate groups. Methods: All patients who delivered between 1st January 2014 to 31st December 2014 were identified based on the parturition register and their case records were analysed for risk factors, intra-partum events, mode of delivery and the indications for caesarean section. These were classified according to the ten group classification system. Results: Caesarean section rate was 41.5% in this period. The CS rate was lowest in Group 3 - 11.97% and 100% in Group 9 (Transverse lie). Group 5 (Previous CS) made the greatest contribution (42.77%) to the total number of CS. Analysing these rates could make comparisons over time and from different centers. Conclusions: Strategies to reduce the CS rate should be concentrated on Group 1 and Group 2. These include a relook at definition of abnormal first stage, standardization of abnormal FHR tracings, strict policy on induction of labour and protocols for trial of labour in previous CS.